Evaluating the Success of the "Arab Awakening" - Shagosh, Tarek (My University, 2012)
The "Arab Awakening" is the recent trend of popular protest in the Middle East resulting in the usurpation of several dictators, extensive political reform, and prolonged conflict. This study examined several possible vulnerabilities contributing to the uprisings of three Arab protest movements, as well as the type of domestic conflict, which came about as a result.
Color poster with text, graphs, and maps.
Keywords: Protest movements--Middle East--21st century; Revolutions--Middle East--21st century; Arab countries--Politics and government--21st century; Middle East--Politics and government--21st century; Revolutions--Arab countries--21st century; Protest movements--Arab countries--21st century; Posters